INVESTIGATING THE ASSOCIATION BETWEEN CEOS COMPENSATION AND DETERMINANTS - Harpreet Kaur, Dr. Lakhwinder Singh Kang (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The present research attempts to analyse company performance, company characteristics, governance structure, and CEOs characteristics, as determinants of CEO compensation in India. A sample of 195 companies is drawn from the firms listed on the National stock exchange of India ltd. (NSE) for the year 2013-2018. A fixed effects panel regression was used to determine the CEO compensation in India. The present study provides an empirical evidence that firm performance (ROA), company size (Assets), and leverage, are significant determinants of CEOs compensation. Whereas, Board size, CEO age, board independence and CEO qualification, have not been found having any influence in deciding the level of compensation being paid to CEOs. This study recommends more reliable results, achieved through a fixed effects panel regression model in panel data.